Status of Invasion to the Personal Space of Citizens by the Persecutor - Ordaeva, Aigul; Balgabay Nakipov, Yernar Shalkharov,; Zhanat Isaeva, Manshuk Imanbekova, (Opción, 2019)
The aim of the study is to investigate the legal status of compulsive harassment, which determines the type of impact, the form of harassment and the level of damage to health via techniques related to an interdisciplinary approach. In result, the stalker maneuvers the types of impact in accordance with a certain phasing, in which he can freely and at his discretion move from the open phase to the closed phase and vice versa depending on the situation. In conclusion, the stalker does not risk first of all conducting any open actions, remaining at the position to be unnoticed